2015
DOI: 10.4103/1319-2442.157336
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C, urinary neutrophil gelatinase-associated lipocalin and N-acetyl-beta-D-glucosaminidase in juvenile and adult patients with systemic lupus erythematosus: Correlation with clinical manifestations, disease activity and damage

Abstract: Lupus nephritis (LN) is a potentially devastating outcome of systemic lupus erythematosus (SLE). It is important to identify reliable, non-invasive methods to assess the kidneys in patients with SLE. The aim of the study was to measure the level of novel markers of renal involvement in these patients and assess their correlation with disease activity and damage. Sixtyone patients with SLE (33 adults and 28 juvenile) were included in the study. Fifty-two ageand sex-matched healthy individuals served as controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Studies of Cys C and b2M in JSLE are scarce; however, our results are consistent with the results of an Egyptian study which reported that serum Cys C was significantly higher in both adults and children with SLE, compared to healthy individuals, adding that its level was also higher in SLE patients with kidney injury. 42 Similar results have been demonstrated in adult patients with SLE, where an increase in serum Cys C has been reported in patients with a history of nephritis even after adjusting conventional measures of renal function. 36,37,43,44 We found that serum Cys C was correlated with conventional markers of renal impairment, as well as indices of disease activity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Studies of Cys C and b2M in JSLE are scarce; however, our results are consistent with the results of an Egyptian study which reported that serum Cys C was significantly higher in both adults and children with SLE, compared to healthy individuals, adding that its level was also higher in SLE patients with kidney injury. 42 Similar results have been demonstrated in adult patients with SLE, where an increase in serum Cys C has been reported in patients with a history of nephritis even after adjusting conventional measures of renal function. 36,37,43,44 We found that serum Cys C was correlated with conventional markers of renal impairment, as well as indices of disease activity.…”
Section: Discussionsupporting
confidence: 77%
“…[ 48 ] As demonstrated in our results, serum Cys C was identified as the most significant predictor of the renal histopathological class, but not of AIs or CIs. While some authors reported a significant association between Cys C and both the damage index and kidney biopsy class,[ 42 ] others were unable to find any role for Cys C in predicting biopsy classes; however, they did not find a correlation between serum Cys C levels and markers of activity or chronicity, either. [ 37 ] To the best of our knowledge, we are the first to study the relationship of serum β2M in children with LN.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there have been nine studies that have investigated the role of the urinary biomarker NGAL, including a large sample size of 581 JSLE patients. However, most of these studies have been focused on UK and US cohorts, with a few studies including Egyptian [ 57 , 58 ] and South African [ 59 , 60 ] JSLE patients; therefore the impact of genetic background and ethnicity has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The same study demonstrated that uNGAL levels were 16-fold higher in patients with biopsy-proven LN than JSLE patients without renal involvement. As well as being a marker of LN, uNGAL has demonstrated its potential application as a marker of LN activity; uNGAL levels (both absolute concentrations and urine-creatinine adjusted concentrations) have been shown to be elevated in active LN and correlated weakly with LN activity [ 44 , 50 , 56 , 57 , 58 , 64 ]. Increased levels of uNGAL are seen with worsening LN and can predate a LN flare by 3–6 months [ 55 , 64 ].…”
Section: Renal Biomarkersmentioning
confidence: 99%
“…Furthermore, Chew et al ( 39 ) reported that cystatin C was highly expressed in patients with a medical history of LN. Cystatin C can be regarded as an important marker in LN ( 40 ). From the Pearson correlation coefficient analysis, a positive correlation between the serum levels of TGF-β1 and cystatin C before and after treatment in the two groups was obtained.…”
Section: Discussionmentioning
confidence: 99%